2011
DOI: 10.1002/biot.201000410
|View full text |Cite
|
Sign up to set email alerts
|

Green fluorescent protein (GFP) leakage from microbial biosensors provides useful information for the evaluation of the scale‐down effect

Abstract: Mixing deficiencies can be potentially detected by the use of a dedicated whole cell microbial biosensor. In this work, a csiE promoter induced under carbon-limited conditions was involved in the elaboration of such biosensor. The cisE biosensor exhibited interesting response after up and down-shift of the dilution rate in chemostat mode. Glucose limitation was accompanied by green fluorescent protein (GFP) leakage to the extracellular medium. In order to test the responsiveness of microbial biosensors to subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
2
20
1
Order By: Relevance
“…These glucose pulses tended to decrease the segregation between the R1 and R2 subpopulations, with a progressive disappearance of the latter subpopulation. This result is consistent with our previous results [23] as well as with other published works [25,29,30], suggesting that substrate limitation induces an increase in cell membrane permeability in order to increase substrate uptake. The value of the automated FC relies upon its generation of on-line, physiologically related variables that enable direct comparisons of these parameters between each other and with process variables.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These glucose pulses tended to decrease the segregation between the R1 and R2 subpopulations, with a progressive disappearance of the latter subpopulation. This result is consistent with our previous results [23] as well as with other published works [25,29,30], suggesting that substrate limitation induces an increase in cell membrane permeability in order to increase substrate uptake. The value of the automated FC relies upon its generation of on-line, physiologically related variables that enable direct comparisons of these parameters between each other and with process variables.…”
Section: Resultssupporting
confidence: 94%
“…This phenomenon was unexpected since GFP would remain in steady-state if the activation of the fis promoter is effectively proportional to the growth rate, suggesting that additional physiological mechanisms are involved. In our previous studies, we have shown that proteins are secreted to the extracellular medium when microbial cells are exposed to prolonged substrate limitation [23,24]. This phenomenon has been reported by several authors and is generally termed protein leakage [25,26].…”
Section: Resultsmentioning
confidence: 91%
“…This is further supported by the high correlation of sensor output (eYFP) and the signal of the integrated plasmid marker (E2-Crimson) shown in Figure 3A, B. Similar correlations were recently described for studies based on a GFP-sensor enabling the detection of carbon-limited conditions in E. coli as well as for a reporter system in yeast, in which the expression of gfp was set under control of a ribosomal protein promoter [37], [38].…”
Section: Discussionsupporting
confidence: 82%
“…Whatever the application is, the scaleup procedures induce a loss of mixing capacity and trigger a stress response at the level of the microbial population. Several authors have reported that this stress response can be beneficial and lead to substantial bioprocess improvement, the origin of which origin remains unclear [26,32,106,107]. In this context, it is important to identify the respective part taken by the individual path and the coordinated heterogeneity hypotheses that have been put forward to explain the appearance of phenotypic heterogeneity in bioprocesses.…”
Section: Biotechnology Journalmentioning
confidence: 99%